2020
DOI: 10.3390/antiox9030246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Enrichment of Corn Oil With alpha- or gamma-Tocopherol on Its In Vitro Digestion Studied by 1H NMR and SPME-GC/MS; Formation of Hydroperoxy-, Hydroxy-, Keto-Dienes and Keto-E-epoxy-E-Monoenes in the More alpha-Tocopherol Enriched Samples

Abstract: The aim of this study is the analysis of the in vitro digestion of corn oil, and of the effect of its enrichment with three levels of gamma- and alpha-tocopherol, by using, for the first time, 1H nuclear magnetic resonance (1H NMR) and a solid phase microextraction followed by gas chromatography/mass spectrometry (SPME-GC/MS). The attention is focused on the hydrolysis degree, the degradation of oil’s main components, the occurrence of oxidation reactions and main compounds formed, as well as on the bioaccessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…To the best of our knowledge, this is the first time that it has been shown that dodecyl gallate and hydroxytyrosol acetate are not able to inhibit lipase activity. The inability of gamma-tocopherol to inhibit lipase activity has been shown in a previous study and the results here obtained confirm this fact [14]. In contrast to this, and although the differences were not significant, a slightly smaller percentage of triglycerides, and a slightly higher percentage of glycerol in the digestates of the enriched samples than in the nonenriched sample was observed.…”
Section: Extent and Pattern Of Lipolysis Produced By The In Vitro Digsupporting
confidence: 90%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first time that it has been shown that dodecyl gallate and hydroxytyrosol acetate are not able to inhibit lipase activity. The inability of gamma-tocopherol to inhibit lipase activity has been shown in a previous study and the results here obtained confirm this fact [14]. In contrast to this, and although the differences were not significant, a slightly smaller percentage of triglycerides, and a slightly higher percentage of glycerol in the digestates of the enriched samples than in the nonenriched sample was observed.…”
Section: Extent and Pattern Of Lipolysis Produced By The In Vitro Digsupporting
confidence: 90%
“…Furthermore, several studies have analyzed the effect that enrichment of certain oils with alpha-tocopherol has on their oxidation when they are submitted to digestion conditions, with controversial results [9,[11][12][13]. Finally, a comparative study of the effect of the enrichment of corn oil with alpha-and gamma-tocopherol showed that the former acts as prooxidant, which is in agreement with some of the aforementioned studies, whereas the second acts as antioxidant [14].…”
Section: Introductionsupporting
confidence: 66%
“…Especially when compared with animal-derived foods, edible plant-derived products are the major source of tocols, such as oil seeds; green parts of plants; whole grains; nuts; and vegetable oils of wheat germen, sunflower, corn, as well as olives [2,[13][14][15][16]. Vegetable oils, quintessential lipid foods in the human diet, are considered very suitable for the enrichment of tocopherols due to the lipophilicity of tocopherols [17]. Besides this, the content of tocols in oil is considered an important indicator to reflect the oil quality.…”
Section: Introductionmentioning
confidence: 99%
“…Both kinds of data are given in Table 1 and Table 2 respectively. As mentioned, data of corn and virgin flaxseed oils were taken from previous studies [ 13 , 14 ]. Regarding data in Table 2 of the molar percentages the different kinds of acyl groups in each oil, it should be mentioned that that although there are four compositional data (%S, %O, %L, %Ln), only three are independent variables.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to lipolysis, lipid oxidation can also take place during digestion [ 9 , 10 , 11 , 12 , 13 , 14 ], leading to the formation of toxic compounds with detrimental effects on health. It may be expected that the extent of this reaction will not be the same for all kinds of oils and that it will be determined by the oxidative stability of the lipids involved as well as by the presence or absence of minor compounds capable of acting as antioxidants or of prooxidants during digestion.…”
Section: Introductionmentioning
confidence: 99%